2022
DOI: 10.1371/journal.pone.0262117
|View full text |Cite
|
Sign up to set email alerts
|

Examining the dynamics of the relationship between water pH and other water quality parameters in ground and surface water systems

Abstract: This study evaluated the relationship between water pH and the physicochemical properties of water while controlling for the influence of heavy metals and bacteriological factors using a nested logistic regression model. The study further sought to assess how these relationships are compared across confined water systems (ground water) and open water systems (surface water). Samples were collected from 100 groundwater and 132 surface water locations in the Tarkwa mining area. For the zero-order relationship in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 45 publications
3
48
0
1
Order By: Relevance
“…In the adsorption process using activated charcoal and zeolite media can bind cations in water such as iron (Fe), aluminum, or magnesium. So that by reducing the metal compounds in it, it will have an impact on increasing the degree of acidity of the water (Saalidong et al, 2022). Water Hardness: Water that has been treated using the media that has been prepared, then the water hardness level is measured using the EDTA titrimetry method (Yan et al, 2022), the results of the hardness level measurement are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…In the adsorption process using activated charcoal and zeolite media can bind cations in water such as iron (Fe), aluminum, or magnesium. So that by reducing the metal compounds in it, it will have an impact on increasing the degree of acidity of the water (Saalidong et al, 2022). Water Hardness: Water that has been treated using the media that has been prepared, then the water hardness level is measured using the EDTA titrimetry method (Yan et al, 2022), the results of the hardness level measurement are shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, when mixing the IGRs and limonoid-based BI produced from neem plants, a reduction in the pH and an increase in the EC of the spray solution were verified. Although this trend is not a rule (Saalidong et al 2022) due to variations in the constituents of the insecticide formulations and their physicochemical properties (including buffer effect), this probably occurred due to the ionization/dissociation of the components in the spraying solution, releasing H+ in the solution that reduced the pH, and others ions that increase the EC. As the botanical formulations used are quite similar in terms of composition and most of IGRs tested are concentrated suspension type formulations, the same trend was observed for the different mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…pH air <6,5 atau pH asam menyebabkan kelarutan logam cenderung tinggi. Air asam juga dapat menimbulkan korosi pada pipa logam [8]. Standar pH air yang baik berkisar antara 6,5 sampai 9,0.…”
Section: Pendahuluanunclassified